THU0481 Sarcoidosis-Is it Only Mimicker or Primary Rheumatic Disease?A Single Center Prospective Study. (23rd January 2014) - Kobak, S.; Sever, F.; Sivrikoz, O.; Orman, M.
Abstract : Background: Sarcoidosis is a chronic systemic inflammatory condition characterized by the presence of noncaseating granulomas. Often the initial presentation of sarcoidosis is rheumatologic, and clinicians should include it in the differential diagnosis of different arthritic, vasculitic, autoimmune, and myopathic syndromes. Objectives: The aim of this study was to determine the clinical, demographic and laboratory data of newly diagnosed patients with sarcoidosis. Methods: BetweenNovember 2011-December 2012, 33 patients reffered for the fırst time to our Rheumatology outpatient clinic with different rheumatic complaints and as result of the investigations were diagnosed with sarcoidosis were included in the study. Within the 13 months follow-up and treatment period, clinical, demographic, laboratory, radiological and histological data were collected and analyzed. Results: 33 patients(7men) were included in the study. Mean age was 46.6 year(20-70year), mean disease duration was 4.3 year(1-25year). The first presenting symptoms of the patients were evaluated; 32 patients had arthralgia, 13 patients had arthritis, 8 patients had erythema nodosum(EN), one patient had muscle weakness, 4 patients had cough, 5 patients had exertional dyspnea, one patient had Raynaud's phenomenon. Systemic organ involvement were evaluated; EN was seen in 15(45.4%), uveitis was seen in 3 (9.09%), myositis was seen in 1(3.03%), neurosarcoidosis was seen in 1(3.03%), arthritis was seen in 26(78.7%) patients. Among 26 patients with arthritis, 22(84.6%) had ankle involvement, 3 (11.5%) had knee involvement, and one patient had involvement of the wrist. There were no patients with cardiac involvement. CT scan of thorax were performed: 11 patients (33.3%) had stage 1, 18 (54.5%) had stage 2, and two (6.06%) had stade 3, and two patients (6.06%) had stage 4 sarcoidosis. Histopathological verification of sarcoidosis with typical non-caseating granulomas were done using endobronchial ultrasound (EBUS) and mediastinoscopic lymph nodes byopsi, as well as skin and axillary lymph node byopsi. Laboratory examinations were performed; increased serum ACE level was seen in 9 (27.3%) patients, increased serum Ca was seen in 3 (9.09%) patient, increased serum D3 was seen in one (3.03%) patient. On serological investigations; nine (27.3%) patients had ANA positivity, 5 (15.1%) patients had RF positivity. Three patients with sarcoidosis overlapping with another rheumatic pathology (Sjögren's syndrome, scleroderma, ankylosing spondylitis). Conclusions: In this study, we have shared clinical and demographic data of 33 newly diagnosed patients with sarcoidosis who were referred with different musculoskeletal complaints. Sarcoidosis can mimic and/or may associated with many primary rheumatic diseases. Recognizing the different rheumatological manifestations of sarcoidosis can lead clinicians to diagnose this condition and start the appropriate therapy. In this regard, further studies are needed. Disclosure of Interest: None Declared